The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1152/japplphysiol.00670.2017
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-targeted antioxidant therapy with MitoQ ameliorates aortic stiffening in old mice

Abstract: Aortic stiffening is a major independent risk factor for cardiovascular diseases, cognitive dysfunction, and other chronic disorders of aging. Mitochondria-derived reactive oxygen species are a key source of arterial oxidative stress, which may contribute to arterial stiffening by promoting adverse structural changes—including collagen overabundance and elastin degradation—and enhancing inflammation, but the potential for mitochondria-targeted therapeutic strategies to ameliorate aortic stiffening with primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
74
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 60 publications
9
74
1
Order By: Relevance
“…; Gioscia‐Ryan et al . ). The thoracic aorta was dissected free of surrounding tissue and sectioned into rings 1 mm in length.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…; Gioscia‐Ryan et al . ). The thoracic aorta was dissected free of surrounding tissue and sectioned into rings 1 mm in length.…”
Section: Methodsmentioning
confidence: 97%
“…; Gioscia‐Ryan et al . ). The boundaries of the elastin‐dominant region (low force region where curvature is ∼0) of the stress–strain curve were determined by fitting a seventh‐order polynomial equation to the data ( r 2 > 0.99; RStudio, Boston, MA, USA) and then calculating the roots of the equation; the first root was considered the boundary between the very low‐force region and the elastin region, and the second root was considered the boundary between the elastin region and the onset of collagen fibre engagement (Lammers et al .…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Preclinical studies have also identified various therapies that have reversed the aging‐associated arterial stiffening in males, such as curcumin (Fleenor et al, ), sodium nitrites (Sindler et al, ), mitochondrial antioxidants (Gioscia‐Ryan et al, ), nicotinamide mononucleotide (de Picciotto et al, ), MR blockade (Kim et al, ), and caloric restriction (Donato et al, ). Several of these therapies—mitochondrial antioxidants (Rossman et al, ), nicotinamide riboside (Martens et al, ), and sodium nitrite (DeVan et al, )—have begun to be translated into studies in healthy older human males and females.…”
Section: Sex Differences In the Impact Of Cvd Risk Factors On Arteriamentioning
confidence: 99%
“…Mitochondrial targeted antioxidants have been shown to improve both large artery stiffness and EDD in old mice and older adults: however, in contrast to the results with TEMPOL described above, these improvements are largely independent of alterations in circulating and aortic cytokine production (Gioscia‐Ryan et al., , ; Rossman et al., ; Zinovkin et al., ). Mitochondrial targeted antioxidants decrease aortic ICAM in old mice (Zinovkin et al., ), and in rat endothelial cells scavenging of mitochondrial ROS attenuates NFκB activity and inflammatory cytokine production (Ungvari et al., ).…”
Section: Interventions To Ameliorate Age‐related Inflammation and Artmentioning
confidence: 97%